Secondary School Biology Teachers’ Knowledge and Practices of Formative Assessment in Tanzania - Ombay, Theodosi; Kikomelo, Sikutegemea; Daniel, Wilson (Central European Journal of Educational Research, 2024)
Using formative assessment (FA) practices in teaching and learning is essential to understanding students’ learning and making informed decisions about students’ academic performance. This study examined secondary school biology teachers’ knowledge and practices of FA in Tanzania. Using a mixed-methods research approach and convergent mixed-methods research design, the study employed simple random and purposive sampling techniques to select the study area and teachers, respectively. A questionnaire and observation checklist used to collect data from 55 teachers in secondary schools. The Statistical Packages for Social Sciences (SPSS) version 26.0 was used to compute descriptive statistics. Findings revealed that though teachers had theoretical knowledge of FA practices, they failed to implement them, particularly Socratic questioning, portfolios, and constructive feedback. This study concludes that teachers did not implement FA practices in the surveyed schools. Thus, there is a need of regular in-service training to develop teachers’ practical competences in FA practices to enhance classroom teaching and students’ learning in biology.